1993
DOI: 10.1007/bf02372550
|View full text |Cite
|
Sign up to set email alerts
|

Side effects of diflubenzuron on a pear psylla predator:Forficula auricularia

Abstract: A series of laboratory, semi-field and field tests showed the high toxicity of diflubenzuron to Forficula auricularia L. nymphs, at concentrations of 15 and 20 g a.i./hl registered in various European countries and the United States to control Cydia pomonella L. Diflubenzuron proved more selective using the 10g/hi concentration registered in France, but several sublethal effects have been observed: morphological abnormalities, reduced weight increase and mobility. Unexpectedly for a chitin-deposit inhibitor, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
1
2

Year Published

1995
1995
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 6 publications
1
36
1
2
Order By: Relevance
“…However, the lack of effect of lufenuron on the predators of WAA is less certain. These results with lufenuron contrast strongly with the known toxicity of diflubenzuron (another chitin synthesis inhibitor) to M. tasmaniae in the field and laboratory (Rumpf et al 1997), and to F. auricularia (Ravensberg 1981;Sauphanor et al 1993). In addition, Shaw et al (1997) reported reduced numbers of M. tasmaniae in the field following the use of oil plus buprofezin (another chitin synthesis inhibitor) when compared with oil alone; and Bueno and Freitas (2004) recorded moulting inhibition in the larvae of another lacewing Chrysoperla externa (Hagen) following treatment of eggs or larvae with lufenuron in the laboratory.…”
Section: Discussionsupporting
confidence: 43%
“…However, the lack of effect of lufenuron on the predators of WAA is less certain. These results with lufenuron contrast strongly with the known toxicity of diflubenzuron (another chitin synthesis inhibitor) to M. tasmaniae in the field and laboratory (Rumpf et al 1997), and to F. auricularia (Ravensberg 1981;Sauphanor et al 1993). In addition, Shaw et al (1997) reported reduced numbers of M. tasmaniae in the field following the use of oil plus buprofezin (another chitin synthesis inhibitor) when compared with oil alone; and Bueno and Freitas (2004) recorded moulting inhibition in the larvae of another lacewing Chrysoperla externa (Hagen) following treatment of eggs or larvae with lufenuron in the laboratory.…”
Section: Discussionsupporting
confidence: 43%
“…Products shown to be safe for earwigs by other workers include B. thuringiensis (Sauphanor et al, 1993), etoxazole (Beliën, 2013), pirimicarb (Ffrench-Constant and Vickerman, 1985;Peusens and Gobin, 2008) and spirotetramat (Shaw and Wallis, 2010, Table 5). …”
Section: Discussionmentioning
confidence: 97%
“…They have been demonstrated to be important predators of many pests orchard including scale insects (McLeod and Chant, 1952;Karsemeijer, 1973), psyllids (Lenfant et al, 1994;Solomon et al, 1999), woolly apple aphid, Eriosoma lanigerum Hausmann (Phillips, 1981;Ravensberg, 1981;Noppert et al, 1987;Mueller et al, 1988;Nicholas et al, 2005;Dib et al, 2010) and codling moth, Cydia pomonella L. (Glen, 1977). For example, excluding earwigs from woolly apple aphid or psyllid infested trees leads to a proliferation of the pests (Mueller et al, 1988;Sauphanor et al, 1993;Nicholas et al, 2005;Gobin et al, 2008). Also, in laboratory tests, He et al (2008) found that earwigs were capable of eating up to 68 apple leaf curling midge, Dasineura mali Keiffer, larvae in a single evening and trees with earwig refuges were more actively foraged for midge larvae than trees without refuges.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Entretanto, alguns autores referem impactos como mortalidade ou distúrbios de desenvolvimento ou reprodução em Amblyseius gossipi (El-Banhawy & Reda, 1988), Chrysopa carnea (Hassan et al, 1987;Zaki & Gesraha, 1987), Deraecoris brevis e Anthocoris nemoralis (Burts, 1983), e Cirrospilus vitratus (Mey, 1988). Efeitos subletais como anormalidades morfológicas e redução do peso corpóreo e da mobilidade foram observadas como efeito do diflubenzuron em Forficula auricularia por Sauphanor et al (1993).…”
Section: Introductionunclassified